The expected, enacted and desired role of family practice nurses in family medicine groups as perceived by nurses and family physicians - Andréanne Bernier; Manon Champagne; Manon Lacroix; Marie-Ève Poitras (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2020)
Introduction: Family practice nurses (FPNs) have been integrated into family medicine groups (FMGs) to improve access to primary care and services. However, FPN workforce development was operationalized without a clear definition of its scope of practice, leading to misunderstandings regarding the achievement of an optimal interdisciplinary teamwork. Objective: To describe the perceptions of the expected role of FPNs by FMG nurses and head physicians in order to better understand the influence of such perceptions on the enacted and desired role of FPNs in FMGs. Methods: Using a descriptive interpretive qualitative approach (Thorne, 2016), 8 registered nurses and 4 head physicians in FMGs were interviewed individually between December 2018 and February 2019. Data were analyzed using the Miles, Huberman and Saldaña's (2014) method. Results: Both groups believe that the expected role of FPNs is to facilitate access to care, as FMGs are one of the entry points into the healthcare system. While several nurses and head physicians perceive that they work collaboratively, hierarchical organizational relationships still continue to shape the enacted role of nurses. Task delegation and subordination activities are more prevalent than integrated collaboration and complementary activities within the interprofessional team. Both groups express different strategies to promote a more effective interdisciplinary teamwork. Discussion and conclusion: All stakeholders must support an optimal interdisciplinary teamwork and maximize the contribution of FPNs to increase patient access to primary care and services.